Pengaruh Likuiditas, Leverage, Profitabilitas Dan Aktivitas Terhadap Pertumbuhan Laba Bersih Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode Tahun 2017- 2022 - Alvita Wahyu Agustin; Sunarto Sunarto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study is to determine the effect of liquidity, leverage, profitability, and activity on profit growth. This research method used 198 data samples from basic industry and chemical subsector companies listed on IDX during 2017- 2022. Analytical techniques using linear regression. From the result of the analysis conducted by the researcher, it was found that leverage is significantly positive for profit growth, profitability is significantly positive for profit growth, liquidity and activity is not significant for profit growth. From the result of the analysis conducted by the researcher, it is expected that further research will be updated and increase the period in order to explain more broadly. Keywords: Profit Growth, Liquidity, Leverage, Profitability, Activity